2016
DOI: 10.1186/s12877-016-0297-z
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index, waist-hip ratio and risk of chronic medical condition in the elderly population: results from the Well-being of the Singapore Elderly (WiSE) Study

Abstract: BackgroundThe aim of the current study was to establish the prevalence and relationship of Body Mass Index (BMI) and Waist-Hip Ratio (WHR) with chronic health conditions and their associated socio-demographic correlates in the elderly population of Singapore.MethodsThe data was extracted from the Well-being of the Singapore Elderly (WiSE) study, a comprehensive single phase, cross-sectional, population-based, epidemiological study conducted in 2013 among Singaporean residents (n = 2565) aged 60 years and above… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 50 publications
(43 reference statements)
4
27
1
2
Order By: Relevance
“…The blood pressure values of the participants in this study were within the normal range, which according to the literature is 121/83-151/93 mmHg in 60-89-yearolds [18]. The waist-hip ratio is used to express abdominal obesity, and for women the risk factor is considered to be > 0.8 [10]. In our study, the mean waist-hip ratio results for both groups were above the threshold.…”
Section: Discussionsupporting
confidence: 67%
“…The blood pressure values of the participants in this study were within the normal range, which according to the literature is 121/83-151/93 mmHg in 60-89-yearolds [18]. The waist-hip ratio is used to express abdominal obesity, and for women the risk factor is considered to be > 0.8 [10]. In our study, the mean waist-hip ratio results for both groups were above the threshold.…”
Section: Discussionsupporting
confidence: 67%
“…BUN was only significantly higher in the DR group than the non-DR group, meanwhile Cr was only significantly higher in the STDR than in the non-STDR group. WHR was thought to be associated with DM 38 and was also thought to be a risk factor for severe DR in women. 39 Our study showed similar results in the univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Results on most other predictors are in the expected direction. Malays were more likely to be overweight compared with other major ethnicities in Singapore, which could explain the higher odds of physician visits among the Malay ethnicity . Given that the Singapore health services require copayment (e.g.…”
Section: Discussionmentioning
confidence: 99%